Reintroducing Akanthomyces ampullifer: providing genetic barcodes, culture, and updated description for the dipteran pathogen rediscovered in Germany - Kubátová, Alena; Kunz, Bernd; Hubka, Vít (Mycoscience, 2025)
The genus Akanthomyces (Ascomycota, Hypocreales) includes entomopathogenic species known to infect a variety of insects and spiders. In this study, we present the first isolate of A. ampullifer characterized by molecular methods, found on dead bodies of the common cave limoniid Limonia nubeculosa (Diptera) in the subterranean spaces of southwestern Germany. In total, seven specimens exhibited distinctive morphological traits that, when compared with historical records, confirm their identification as A. ampullifer-particularly noted for its affinity to dipteran hosts. Absent from culture collections and molecular repositories, this species has eluded detailed scientific documentation using modern methods. Our research bridges this knowledge gap, providing the first genetic identification barcodes of five genes, living culture, cultivation requirements, and an updated description. This overlooked fungus is phylogenetically most closely related to the species A. pyralidarum, A. laosensis, and some other species mostly associated with adult moths. It demonstrates a unique morphological signature with monoblastic phialides forming a layer on the surface of synnemata and produces long, cylindrical, chain-forming conidia. It prefers lower temperatures, exhibiting an inability to grow at 25 °C, coupled with notably slow growth in culture.
Keywords: Limonia nubeculosa; entomogenous fungi; Cordycipitaceae; crane flies; multigene phylogeny